Curva tensional ocular fisiológica diária e proposição da mini curva correlacionadas com os níveis circadianos de cortisol sanguíneo em ovinos - Farencena, Fernanda Iensen (2022)
Intraocular pressure (IOP) is checked using tonometry, which helps in the diagnosis of diseases that lead to hypotension or ocular hypertension. Being, uveitis and glaucoma, the main eye diseases that alter IOP and generate the need for an early diagnosis and treatment for more satisfactory results and patient comfort. It is known that this test is still little used in the routine of production animals, because, in the literature, there are few data on the subject. For a reliable diagnosis of diseases that cause changes in IOP, it is necessary to have knowledge of the normal values of this parameter and its physiological variations at different times of the day. The objective of the test was to analyze the IOP values during a period of 24 hours, obtaining data for the elaboration of the daily tension curve (CTD) and mini curve of the sheep species. In addition, compare the IOP with the cortisol levels of the studied species, in each hour during a period of one day, in order to correlate the data of these two variables. This study was carried out with the number of animals suitable for this proposal, being 12 Texel ewes, under minimal restraint and in their natural habitat, aiming at minimal external interference in the data presented. With this, it was possible to affirm that there is no statistically significant difference between the IOPs of the right eye (OD) and left eye (LE), considering the 24 measurements performed over 24 hours. However, in the values of the IOPs of both eyes, every hour, there was a statistically significant difference between different times of the day. Furthermore, the maximum and minimum IOP peaks during the 24 hours of the day followed the cortisol levels at the same times. In addition, these variables were correlated with the daily luminosity rate. After analyzing the data obtained, it was possible to determine the physiological CTD of Texel sheep, noting a positive feedback relationship between IOP and blood cortisol rates. Then, a mini daily tension curve was proposed, with IOP measurements at 04:00h (average IOP value), at 12:00h (maximum IOP peak) and at 22:00h (minimum IOP peak).